Use of Monitoring Tests Among Patients With Localized Prostate Cancer Managed With Observation. Issue 4 (8th April 2023) - Leapman, Michael S.; Wang, Rong; Loeb, Stacy; Seibert, Tyler M.; Gaylis, Franklin D.; Lowentritt, Ben; Brown, Gordon A.; Chen, Ronald; Lin, Daniel; Witte, John; Cooperberg, Matthew R.; Catalona, William J.; et al.
Abstract : Purpose: It is unknown whether compliance with recommended monitoring tests during observation of localized prostate cancer has changed over time. Materials and Methods: We performed a retrospective cohort study of Medicare beneficiaries diagnosed with low- or intermediate-risk prostate cancer in 2004-2016 who were initially managed with observation for a minimum of 12 months. The primary objective was to examine rates of PSA testing, prostate biopsy, and prostate MRI. We used multivariable mixed effects Poisson regression to determine whether rates of PSA testing and prostate biopsy increased over time. In addition, we identified clinical, sociodemographic, and provider factors associated with the frequency of monitoring tests during observation. Results: We identified 10, 639 patients diagnosed at a median age of 73 (IQR 69-77) years. The median follow-up time was 4.3 (IQR 2.7-6.6) years after diagnosis. Among patients managed without treatment for 5 years, 98% received at ≥1 PSA test, 48.0% ≥1 additional prostate biopsy, and 31.0% ≥1 prostate MRI. Among patients managed with observation for ≥12 months, mixed effects Poisson regression revealed that rates of PSA testing and biopsy increased over time (per calendar year: RR 1.02, 95% CI: 1.02-1.03 and RR 1.10, 95% CI: 1.08-1.11, respectively). Clinical and sociodemographic factors including age, clinical risk, race/ethnicity, census tract poverty, and region were associated with rates of biopsy and PSA testing. Conclusions: Use of recommended monitoring tests including repeat prostate biopsy remains low among Medicare beneficiaries undergoing observation for low- and intermediate-risk prostate cancer.